Trigeminal Neuralgia Due to a Small Meckel's Cave Epidermoid Tumor: Surgery Using an Extradural Corridor - Furtado, Sunil V. (Thieme Medical Publishers, 2009)
Tumors at the petrous apex are associated with a variety of symptoms, which most often involve the trigeminal nerve. The authors present a rare case of a small epidermoid tumor in Meckel's cave that caused medically refractory trigeminal neuralgia. The surgical challenge associated with approaches to such lesions is discussed. The skull base tumor was excised completely through a small temporal craniotomy. The practicality of neuronavigation in reaching the petrous apex using a small extradural window is presented.